Entre Vienne, Londres et Berlin-Est : Eva Schmidt-Kolmer et la genèse transnationale des crèches est-allemandes - Michel Christian (Recherches en Éducation)
East German day nurseries have been at the center of debate in Germany before and after 1989. This article aims at providing a non-German view on that debate. It emphasizes the fact that the development of day nurseries in East Germany, even if pushed further than in any other country in the world, did not happen independently of the other European countries. This article focuses on the transnational dimension of East German day nurseries by high-lighting the trajectory of the woman who inspired their development: Eva Schmidt-Kolmer. Born in Vienna, Austria where she grew up, she emigrated to England in 1938 and settled down in East Germany in 1946. She accumulat-ed enough resources to become a transnational actor in the area of early childhood and to make her views on day nurseries prevail in her country. This article makes the case not only for the internationalization of East German day nurseries’ history but also for its normalization within a shared European history